Analisis Perhitungan Harga Pokok Produksi Menggunakan Metode Full Costing Pada Industri Rumahan Bawang Goreng Barokah - Triyas Putri Wardani; Anita Kartika Sari; Rika Yuliastanti (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The full costing method is an approach in the calculation of the cost of production that includes all elements of production costs, namely the cost of raw materials, direct labor, and factory overhead costs, both variable and fixed. This research was conducted on the Barokah Fried Onion Home Industry, which produces red fried onions and white fried onions, with the aim of analyzing the comparison of the calculation of the cost of production between the simple method and the full costing method. This study uses a qualitative method with a descriptive approach. The data used consisted of primary and secondary data, which were obtained through data collection techniques in the form of observation, interviews, and documentation. The results of the study show that there is a difference in the calculation of the cost of production between the simple method and the full costing method. In red fried onion products, the simple method produces a cost of production calculation of Rp2,022,000, while the full costing method produces Rp2,045,249. Meanwhile, in white fried onion products, the simple method produces a cost of production of Rp833,500, while the full costing method produces Rp846,452. The difference in calculation is due to the absence of several components of factory overhead costs in the simple method. such as equipment depreciation costs, transportation costs, and equipment maintenance costs. Based on the results of the study, it can be concluded that the full costing method provides more accurate results in calculating the cost of production compared to the simple method. Thus, the full costing method can be used as a more appropriate approach in determining the cost of production effectively and comprehensively.